EUROPEAN ECONOMY FROM THE ATLANTIC TO THE URAL(ECONOMIC FORUM IN KRYNICA GÖRSKA, POLAND: INFORMATION, SPECULATIONS, IDEAS) - Savelyev, Yevhen; Hladiy, Iryna; Kurylyak, Vitalina (Journal of European Economy, 2018)
Thus far not a single monograph or study has analyzed the European economy as an economy of a continent. An international economic forum held yearly in Krynica Gorska, Poland, is one of few sources for such information. In spite of being traditionally called “the second Davos”, it is unique in view of its primary objective, which is to settle the problems of economic growth in Central and Eastern Europe. Obviously, a profound examination of the diversified phenomena in the European economy is impossible to conduct within a single forum. However, every year the organizers succeed in determining its urgent problems and searching out personalities capable of formulating its major regularities within the common European dimension. This can also be attributed to the last, thirteenth forum, which took place on September 4-6, 2003.